2019
DOI: 10.3390/s20010076
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Reduced Graphene Oxide-Based Screen-Printed Electrodes for Total Tetracycline Determination by Adsorptive Transfer Stripping Differential Pulse Voltammetry

Abstract: Disposable electrochemically reduced graphene oxide-based (ERGO) screen-printed electrodes (SPE) were developed for the determination of total tetracyclines as a sample screening approach. To this end, a selective adsorption-detection approach relied on adsorptive transfer stripping differential pulse voltammetry (AdTDPV) was devised, where the high adsorption capacity and the electrochemical properties of ERGO were simultaneously exploited. The approach was very simple, fast (6 min.), highly selective by comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Biorecognition is one of the most common strategies and uses aptamer-based sensors [23][24][25][26][27][28][29][30][31][32], which are the most recent and commonly found in the literature, followed by enzyme-linked immunoassay (ELISA) functionalization [14,15,33,34], and sensors based on molecular imprinted polymers (MIPs) [35,36] or antibodies [8,37,38] (see Table S2). Furthermore, the oxidation of TCs has been reported using diverse types of electrodes and materials, ranging from metallic nanoparticles [39][40][41][42][43][44][45], graphene oxide [46][47][48][49][50], composites [43,[51][52][53][54][55], gold [3,11,56], boron-doped diamond electrode (BDDE) [57][58][59][60], ruthenium oxide-hexacyanor-uthenate (RuO-RuCN) [61], or multiwall carbon nanotubes (MWN...…”
Section: Introductionmentioning
confidence: 99%
“…Biorecognition is one of the most common strategies and uses aptamer-based sensors [23][24][25][26][27][28][29][30][31][32], which are the most recent and commonly found in the literature, followed by enzyme-linked immunoassay (ELISA) functionalization [14,15,33,34], and sensors based on molecular imprinted polymers (MIPs) [35,36] or antibodies [8,37,38] (see Table S2). Furthermore, the oxidation of TCs has been reported using diverse types of electrodes and materials, ranging from metallic nanoparticles [39][40][41][42][43][44][45], graphene oxide [46][47][48][49][50], composites [43,[51][52][53][54][55], gold [3,11,56], boron-doped diamond electrode (BDDE) [57][58][59][60], ruthenium oxide-hexacyanor-uthenate (RuO-RuCN) [61], or multiwall carbon nanotubes (MWN...…”
Section: Introductionmentioning
confidence: 99%
“…The addition of molecules such as (-Cl) or (-OH) determines the derived names of CTC or OTC, for instance. However, all tetracyclines contain a phenol group that makes them electroactive substances [54]. The chemical properties of CTC, OTC, TC and DC are summarised in Table 3 below.…”
Section: Chemical and Biological Properties Of Tetracyclinesmentioning
confidence: 99%
“…In a brief overview of Table 1 it can be easily observed that GCE transducers were selected in most studies as a substrate for subsequent modifications as they are widely used in electrochemistry due to their robustness, well characterized surface properties, and easy modification. Alternatives to their use were based on Pt [ 80 ], Au [ 86 ], FTO [ 83 ], and on the miniaturized and versatile 3-in-1 screen-printed electrodes [ 72 , 73 , 89 , 90 ]. Regarding the detection technique, DPV was frequently employed due to its superior sensitivity, followed by LSV.…”
Section: Nanostructured Carbon-based (Bio)sensors For Pharmaceuticmentioning
confidence: 99%
“…Despite its robustness and reliability, this conventional electrode is more suitable for laboratorial work rather for in-situ environmental applications due to its bulkier dimensions. In this sense, screen-printed electrodes [ 72 , 73 , 89 , 90 , 140 , 151 ] and the film type electrodes of gold [ 109 ] and FTO [ 83 ] present high area-to-volume ratio enabling miniaturization and portability and, therefore, are more convenient for in loco analysis. In this miniaturization process, carbon nanomaterials can be extremely useful and exceptionally reliable through the production, for example, of buckypaper type electrodes.…”
Section: Overall Comparison Between Reported Nanostructured Carbonmentioning
confidence: 99%
See 1 more Smart Citation